YiQiFuMai Powder Injection ameliorates the oxygen-glucose deprivation-induced brain microvascular endothelial barrier dysfunction associated with the NF-κB and ROCK1/MLC signaling pathways. (13th May 2016) - Cao, Guo-sheng; Chen, Hong-lin; Zhang, Yuan-yuan; Li, Fang; Liu, Chun-hua; Xiang, Xiang; Qi, Jin; Chai, Cheng-zhi; Kou, Jun-ping; Yu, Bo-yang
Abstract: Ethnopharmacological relevance: YiQiFuMai Powder Injection (YQFM) is a modern preparation derived from Sheng-mai San, a traditional Chinese prescription, widely used for the treatment of cardiovascular and cerebrovascular diseases. However, its potential molecular mechanism remains unclear. Aim of the study: The present study was designed to observe the effect of YQFM on oxygen-glucose deprivation (OGD)-induced the brain microvascular endothelial barrier dysfunction and to explore the underlying pathways in vitro . Methods: A mouse brain microvascular endothelial cell line (bEnd.3) was subjected to OGD (2–9 h) to examine the efficacy and molecular mechanisms in the presence or absence of YQFM (100, 200 and 400 μg/ml). Results: The results of 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and Trans-endothelial electrical resistance (TEER) assays demonstrated that treatment with YQFM increased the cell viability and TEER value, decreased even blue (EB) albumin leakage after OGD in bEnd.3 cells. Western blotting and immunofluorescence staining showed that YQFM reduced the breakage and translocation of Zonula occludens-1 (ZO-1) and claudin-5 after 4 h of OGD and decreased the expression of these proteins after 9 h of OGD. Moreover, YQFM significantly inhibited the expression, phosphorylation and nuclear translocation of NF-κB/p65 and decreased the expression of intercellular adhesionmolecule-1 (ICAM-1) and cyclooxygenase (COX-2) as well as production of nitric oxide (NO). In addition, real time-PCR results revealed that YQFM suppressed the mRNA levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) after 4 h of OGD. Furthermore, YQFM markedly inhibited both the phosphorylation of myosin light chain (MLC) and cytoskeletal reorganization and reduced the expression of cleaved-ROCK1 in bEnd.3 cells subjected to OGD. Conclusion: These findings suggest that YQFM ameliorates the OGD-induced brain microvascular endothelial cell barrier disruption associated with the NF-κB/p65 and ROCK1/MLC signaling pathways. These data provide new insights into the use of this preparation for treating cerebrovascular diseases. Graphical abstract: